Democracy and the people empowerment (Part II) (2015)
The concept, of empowerment of the people, is understood as a political process that involves the people selecting their leaders, making meaningful contributions to decision-making as members of a population and gaining absolute control over the system that produces their representatives. This artic 1 e is a continuation of 'Democracy and People Empowerment (Part I) publisher earlier, briefly reviews how power developed or was acquired by the people c: Athens. The work emphasises to what extent the non-altruistic background: the emergence of the demos as apolitical force in the Athenian direct democracy threatened the supremacy of the people. As the demos stirred the political ship c : Athens, evidence of their being manipulated by selfish elements c: undemocratic descents persisted and this ancient trend provides a parameter for explaining what sometimes undermines the empowerment of the people in modem representative democracy where broader participation is encouraged While people may have the power to thumbprint in elections or express their wishes through speeches, the article, using contemporary examples particularly from Nigeria, indicates how the 'original impetus' that is scarcely selfless continues to impede empowerment of the people. This is a picture of the power that marginalises, disenfranchises or refuses to let the power of the people out in a democracy.